PRICE AS A STRATEGIC TOOL FOR CUSTOMER RELATIONSHIP MANAGEMENT: INTEGRATING VALUE-BASED AND DYNAMIC PRICING - SAVCHENKO, Olena; HREKOV, Mykhailo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article argues that combining Value-based pricing (VBP) and Dynamic Pricing (DP) approaches is a relevant, customer-oriented management model. The mechanism of this combination is based on a deep understanding of consumer behaviour (through predictive AI analytics) and adherence to ethical standards. VBP is a strategic imperative that ensures value-based pricing, while AI-enhanced DP is a technological mechanism that allows the VBP philosophy to be put into practice by adjusting prices in real time according to individual value and willingness to pay.The authors emphasise that there are fundamental differences in the approaches to implementing dynamic pricing strategies between the B2B and B2C sectors. These differences are due to the different nature of relationships, decision-making processes and target settings in each market. Thus, B2B pricing is contract-bound and aims to maintain stable margins and customer profitability, while B2C pricing responds to instant demand, seeking to maximise immediate revenue and sales volumes. The B2B sector uses rational mechanisms such as cost indexation (to protect margins) and customer-oriented matrices (to account for relationship profitability), with a priority on price consistency and transparency. In contrast, the B2C market dominates through psychological and personalised tactics, with a priority on responding quickly to demand and competition.  Also, the B2B sector requires deep system integration (ERP, CRM) to ensure contract compliance, and the complexity and high cost of transactions lead to hybrid solutions (algorithms and judgement) where the value of relationships outweighs immediate profit. In contrast, B2C relies primarily on algorithms and simpler integration with e-commerce platforms.The complementarity of VBP and DP creates a powerful hybrid approach, with VBP providing a fair, value-oriented pricing basis that protects trust, while DP prevents profit loss due to the inability to adjust prices quickly. Thus, integration allows a company not only to justify a high price with the value of the product, but also to maximise revenue by responding quickly to fluctuations in variables. Along with the importance and relevance of this symbiosis, it is important to strengthen the theoretical justification of this process, as well as to develop practical mechanisms to ensure the positive mutual influence of approaches in different sectors of operation (B2B and B2C).
Keywords: price; value-based pricing; consumers; consumer loyalty; customer-oriented management; dynamic pricing; modern information technologies